Risk analysis of thyroid cancer incidence after exposure in childhood in the most contaminated areas of Ukraine, Belarus, and Russia in comparison with other studies. (18th April 2006) - Goulko, G.; Tronko, M.; Bogdanova, T.; Henrichs, K.; Kayro, I.; Shpak, V.; Lassmann, M.; Reiners, Chr.
The current knowledge about thyroid cancer induction due to 131 I exposures during childhood is limited. Due to the low incidences observed, it was assumed that 131 I is less effective in cancer induction by a factor of 3, if compared to external exposures. An increase of the thyroid cancer incidence among children and adolescents from the south-eastern Belorussian, the northern Ukrainian, and the western Russian oblasts after the reactor accident in Chernobyl is reported. As a result of the further improvement of the dose estimation methods, the individual exposure doses based on the results of direct thyroid activity measurement were recalculated, and the geographical pattern of age-dependent thyroid doses was analysed. These resulted in the re-assessment of collective doses and of thyroid cancer risk.